Особливості архітектурно планувальних та містобудівельних рішень при проектуванні будівель в умовахщільної забудови - Петренко, Ю. В.; Petrenko, Yu. (Видавництво Львівської політехніки, 2017)
У статті проаналізовано основні підходи до архітектурної організації простору в умовах насиченої забудови. Розглянуто особливості функціонування і взаємозв’язку між наявними будівлями та новобудовами. Описано пропозиції формування простору та проблеми, що виникають у процесі будівництва в умовах щільної забудови.

In this article the main approaches to architectural space organization in terms of intense development. The features and functioning of the relationship between existing buildings and new buildings. Described offers space formation and problems arising during the construction in a dense housing. A characteristic feature of modern architectural and urban development in Ukraine the formation of multi-housing and public facilities, creating new types of facilities maintenance, reconstruction and modernization of residential areas, new building technologies in the construction of buildings. All this makes the sealing of existing buildings, including how to improve storeys of residential and public buildings and building vacant lots adjacent to existing buildings. Modern architects, city builders, sociologists, urban justify ramming several reasons. So demographers attribute the problem of overpopulation of the planet, a sharp increase in population growth. If in 1900 in the world population more than 1 billion people, in 2006 nearly 6.5 billion, and by 2050 the population is projected to increase to 12 billion. Sociologists suggest that apartments and offices on the upper floors are especially popular among young businessmen, actors, architects, designers and other representatives of business and creative young people with an active lifestyle for which residence and work has significant practical value and image. In residential tower sare typically designed and built prestigious penthouse – original villaonto pof a building which overlook stheurban and natural environment. For the sereasons, high-rise apartment complexe sareparticularly attractive when they are placed in both the downtown and the city on the banks of rivers, lakes and forested surroundings. In town-planning aspect for high-rise and composition make it possible to identify a large scale of urban development, the central focus areas and other significant planning units. At the same time, modern civil construction investors in Ukraine are considering increasing the heights of buildings mainly for the purpose of sustainable development of urban areas and conserve resources for the construction of engineering and transport networks, excluding a number of problems that arise while
Features of architectural planning and urban planning decisions of the design of buildings in a dense housing
Keywords: щільна забудова; житловий комплекс; взаємодія; взаємний вплив; перенасичення; земельна ділянка; dense buildings; residential complex; mutual influence; saturation; land; 728.1; 72.012